2022
DOI: 10.17221/171/2021-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endophytic bacterium, Stenotrophomonas maltophilia JVB5 on sunflowers

Abstract: Identifiable endophytic bacteria with plant growth-promoting traits promise to ensure sustainable agriculture. However, information on the versatility and exploration of sunflower-associated bacteria as bioinoculants is less studied. Here, we present the whole-genome sequence and annotation of Stenotrophomonas maltophilia JVB5 isolated from the sunflower root endosphere from the North West province, South Africa. The whole-genome analysis revealed a genome size of 4 771 305 bp, a sequence read count of 8 764 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…The isolated bacteria belonged to three phyla namely, Proteobacteria (seven bacterial isolates), Firmicutes (two bacterial isolates) and Actinobacteria (one bacterial isolate). However, diazotropic diversity reported in our study was found to be similar to the results of earlier researchers among various species of genera such as Bacillus, Stenotrophomonas, Pseudomonas, Microbacterium in rice, maize, sun ower, tuber and root crops (Ki e and Laing 2016, Duque and Villordon 2019, Adeleke et al 2022. Two rhizospheric bacterial isolates M. subterraneus and B. nasdae, were not reported earlier as rhizospheric bacterial isolates while their rst isolation was from the Australian thermal aquifer and condensation water from Mir, Russian space station respectively (Tan et al 2017, Li et al 2017.…”
Section: Discussionsupporting
confidence: 91%
“…The isolated bacteria belonged to three phyla namely, Proteobacteria (seven bacterial isolates), Firmicutes (two bacterial isolates) and Actinobacteria (one bacterial isolate). However, diazotropic diversity reported in our study was found to be similar to the results of earlier researchers among various species of genera such as Bacillus, Stenotrophomonas, Pseudomonas, Microbacterium in rice, maize, sun ower, tuber and root crops (Ki e and Laing 2016, Duque and Villordon 2019, Adeleke et al 2022. Two rhizospheric bacterial isolates M. subterraneus and B. nasdae, were not reported earlier as rhizospheric bacterial isolates while their rst isolation was from the Australian thermal aquifer and condensation water from Mir, Russian space station respectively (Tan et al 2017, Li et al 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Better still, there is a need to develop robust bioinformatics tools and analytical techniques with the existing technologies to generate microbiome data as a guide for further experiments. Adeleke et al [ 40 ] and Adeleke et al [ 157 ] reported the genomic characterization of plant growth-promoting endophytic bacteria, Bacillus cereus T4S and Stenotrophomonas maltophilia JVB5 as copious sunflower growth enhancers. Furthermore, effort on the use of these endophytic bacteria as biocontrol agent against phytopathogens is expected to be investigated in the future studies.…”
Section: Current Status Of Plant Microbiome Collaborative Researchmentioning
confidence: 99%
“…Te concentration of IAA produced by the S. maltophilia strain is considered low. However, the addition of diferent concentrations of L-trp contributed signifcantly to the increase in IAA production, ranging from 3.9 μg/mL to 2.5 mg/mL [30,[32][33][34]36]. Growth of the bacterium in LB medium spiked with L-trp as a precursor at a concentration of 25 ug/mL produced a 24% increase in IAA within 24 h. It was also observed that higher concentrations (100-400 ug/ mL) of the precursor increased IAA production to 79 ± 2.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that S. maltophilia can promote plant growth, stimulate pathogen control, and increase plant tolerance to different types of stresses due to the production of phytohormones such as IAA and protective enzymes [ 35 ]. Adeleke et al [ 36 ] demonstrated that genes such as trp ABCD, ami E, and mia A present in this bacterium were related to IAA synthesis through the indole-3-acetamine pathway.…”
Section: Resultsmentioning
confidence: 99%